Investigating Social Elements of Human Literacy to Become Educators of Children with Special Needs in Inclusive Preschools - Suri Handayani Damanik; Salsabila Hasiana Tanjung; Ibnu Hajar; Kamtini; Lucia Voni Pebriani (PT. Global Research Collaboration, 2026)
This study analyses the social aspects of human literacy among Early Childhood Education Program (ECEP) students in Medan to support children with special needs in inclusive settings. Using a descriptive quantitative design, data were collected from 127 fourth-year students through a 48-item questionnaire covering six indicators: justice, respect, care, leadership, relationship-building, and communication. The results show that students’ social human literacy is in the “good” category (M = 3.21). Care (empathy) and communication scored the highest, indicating strong interpersonal sensitivity in supporting diverse learners, including children with special needs. However, social leadership was the lowest, suggesting limited readiness in initiating and managing inclusive practices. Overall, students demonstrate moderate to strong readiness for inclusive education, but improvements are needed in leadership and action-oriented competencies. The study highlights the importance of integrating experiential learning in teacher education to better prepare inclusive educators.